Pengetahuan dan sikap dengan kepatuhan protokol kesehatan 5 M di masa Pandemi Covid-19 - Muhammad Ricko Gunawan; Rilyani Rilyani; Triyono Triyono (Holistik Jurnal Kesehatan, 2021)
The knowledge, attitude, and compliance: Implementation of health protocol policy in Covid-19 prevention Background: The World Health Organization as Public Health Emergency of International Concern, PHEIC) has designated coronavirus Disease–19. The ways to transmit Covid-19 is through hand contact and hand hygiene, the most effective way to prevent nosocomial infections by attitude and knowledge of nurses play an important role in implementing the implementation of hand hygiene in a health facility environment. Since the pandemic the behavior of nurses has changed significantly, nurses' knowledge of the chain of transmission of the Covid-19 disease has increased, one of which is through hand contact.Purpose: To identify the relationship of knowledge, attitude, and compliance: Implementation of health protocol policy in Covid-19 preventionMethod: A quantitative with observation and questioners and uses a Cross-Sectional approach. The design of this study uses a survey and the population in this study were all visitors and employees as many as 120 respondents at the Kemiling Health Center, with total sampling.Results: Based on the results, the average age of the respondents was 41 years with a value (mean) of 34.9±6.28 with 78 (65%) female gender and high school education (58 (48.3%) patient and family respondents 42 (35%). Civil service respondents' occupations 44 (36.7%) information got from television 61 (50.8%) the length of information got by respondents was 15 months with a value (mean) of 13.82±2.52. Respondents' knowledge was poor 73 (60.8%) attitude of respondents did not support 78 (65.0% It concluded that there is a relationship between demographic data and Implementation of health protocol policy in Covid-19 prevention with the Chi-Square statistical test with a p-value = 0.000≤ 0.05. The attitude of respondents at risk is 10,681 times greater for compliance with the 5M Health protocol at Kemiling Health Center Bandar Lampung.Conclusion: There is a significant relationship of knowledge, attitude, and compliance: Implementation of health protocol policy in Covid-19 prevention. Recommendation for Health Center management to do health promotion and straightly health protocols.Keywords: The knowledge; Attitude; Compliance; Implementation; Health protocol policy; Covid-19 prevention.Pendahuluan: Corona Virus Disease – 19  telah ditetapkan oleh WHO (World Health Organization) atau Badan Kesehatan Dunia sebagai Kedaruratan Kesehatan Masyarakat yang Meresahkan Dunia (KMMD).  Penularan Covid-19 salah satunya adalah melalui kontak tangan dan hand hygiene merupakan cara yang paling efektif dalammencegah terjadinya infeksi nosokomial,namun pelaksanaan handhygienebelum mendapatkan respon yang maksimal dari petugas kesehatan. Sikap dan pengetahuan perawat menjadi peran penting dalam menerapkan pelaksanaan hand hygiene di lingkungan fasilitas kesehatan. Sejak pandemi perilaku perawat mengalami perubahan dengan signifikan,  meningkatnya pengetahuan perawat akan rantai penularan penyakit Covid-19 yang salah satunya melalui kontak tangan.Tujuan : Mengetahui adanya hubungan yang mempengaruhi sikap dan pengetahuan terhadap kepatuhan protokol Kesehatan 5M  selama masa pandemi Covid-19 di Puskesmas Rawat Inap tahun 2021.Metode: Penelitian kuantitatif dengan metode observasi analitik dan menggunakan pendekatan Cross Sectional. Rancangan penelitian ini menggunakan survey. Populasi dalam penelitian ini adalah seluruh pengunjung dan pegawai sebanyak 120 responden di Puskesmas Kemiling menggunakan total sampel.Hasil : Didapatkan bahwa rata-rata usia  responden 41 tahun dengan nilai (mean) 34.9±6.28 dengan jenis kelamin perempuan sebanyak  78 (65%) dan Pendidikan SMA (58 (48.3%) responden pasien dan keluarga 42 (35%). Pekerjaan responden PNS 44 (36.7%) informasi yang didapat dari televisi 61(50.8%) lama informasi yang didapat responden 15 bulan dengan nilai (mean) 13.82±2.52. Pengetahuan responden buruk 73 (60.8%) sikap responden tidak mendukung 78 (65.0%). Dapat disimpulkan ada hubungan antara data demografi dengan kepatuhan protocol Kesehatan 5M dengan uji statistik Chi-Square dengan nilai p-value = 0,000≤ α 0,05  sikap responden beresiko 10.681 kali lebih besar terhadap kepatuhan protocol Kesehatan 5M di Puskesmas Kemiling Bandar Lampung.Simpulan :Ada hubungan yang bermakna antara sikap dan pengetahuan dengan kepatuhan terhadap protokol kesehatan selama masa pandemi Covid-19 di Puskesmas Rawat Inap Kemiling Tahun  2021. Disarankan bagi Puskesmas Rawat Inap Kemiling mengutamakan  program In House Training atau Pelatihan PPI Dasar bagi petugas Kesehatan dan memperketat protocol kesehatan.